Uncovering the cultural dynamics in mentoring programs and relationships : enhancing practice and research - Kochan, Frances K.; Kent, Andrea M.; Green, André M., 1973- (Mentoring perspectives., 2015)
Although cultural issues have a powerful influence on the failure and success of mentoring programs and relationships, there is scant research on this area and little in the way of guidelines that practitioners can use to help assure mentoring success. This book seeks to expand our knowledge and understanding of this topic and to foster the use of this information to enhance practice and research.The book is unique in a number of ways and will be an important resource for all those engaged in mentoring endeavors and for those conducting research in this area. First, it presents research findings on the cultural impact of mentoring at the individual relational level, at the organizational level, and within the structures of the society. Secondly, the chapters describe mentoring from an international perspective including programs from Africa, Australia, Canada, Finland, India, Ireland, Korea, Scotland, Sweden and the United States. Third, the book is research based and yet, can be easily applied to practice. Chapters provide information on lessons learned and also include reflective questions to enable the reader to delve more deeply into the constructs and findings in order to apply them to their own practice and research. This makes the book an ideal resource for training mentors and mentees, for designing mentoring programs, for teaching about mentoring, and for establishing and maintaining mentoring relationships. It also will be of value to those who are engaged in conducting research on how to create and maintain successful mentoring relationships and programs.